The cooperation of author and illustrator in popular strorybooks in English language - Csizmadia, Gábor (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2023)
This study tackles the relationship between the texts of children’s books and their illustrations, the possibilities and traditions of cooperation between author and artist, while attempting to provide insight into the world of criticism published in the field in the past two decades. Though the corpus of literary theory and criticism created in connection with children’s books and their illustrations still owes us major reference material, as frequently mentioned by advocates of the theme, this study is confined to mentioning the most exciting points of discussion. This is supposed to build a background for the browsing which attempts to illustrate the theoretical treatises with a reminiscence on a few outstanding participants of the history of British, American and international children’s books, their work and the interesting developments of author-artist cooperation.
Keywords: children's books; illustration; artwork; design